Stock Price Reaction to Earnings Announcement: Case of an Emerging Market - Iqbal, Javed; Farooqi, Faraz Ahmed (JISR management and social sciences & economics, 2014)
Disclosure of financial statements by corporate firms is an important requirement of good corporate governance practice. This information is crucially important for rational decision making by investors who are willing to invest in stock of the firm based on fundamentals of the company. The speed with which this information is absorbed to stock prices is an important determinant of market efficiency. In a semi strong form efficient stock market the prices instantaneously and accurately adjust to new information. This paper conducts an event study analysis on an emerging market namely the Karachi Stock Exchange (KSE) by investigating the stock price reaction to public announcement of quarterly after tax profit by listed firms. By employing five year data on stock prices from January 2004 to August 2008 for 114 non financial firms it was found that information about earnings are quickly absorbed in prices before earning announcement is made so that there is no abnormal return post earnings announcement. Moreover the study provides evidence that there is a bigger element of surprise in bad news than in good news as the market reaction to bad news is stronger. A stronger reaction to bad news means that investor’s interpretation of earnings news is homogenous.